Penyusunan Model Cryptocurrency yang Sesuai Syariah - Hendra Setiawan (Khazanah Multidisiplin, 2025)
This study discusses a cryptocurrency model that is in accordance with Islamic sharia principles. The study was conducted using a qualitative method involving interviews with experts in digital technology and Islamic finance, as well as secondary data analysis from various literatures. The results of the study show differences in the views of scholars regarding the permissibility of cryptocurrency, where some state it is halal, some are haram, and others are neutral. The elements that make cryptocurrencycontroversial in sharia include uncertainty, excessive speculation, and the absence of supporting assets. This study offers a halal cryptocurrency model that is free from gharar, maysir, has supporting assets, is under the supervision of sharia authorities, is transparent, safe, free from usury, and is supported by fatwas. This model aims to provide a halal alternative for Muslims in transacting using modern cryptocurrency technology.